Chattooga : descending into the myth of Deliverance river - Lane, John, 1954- (University of Georgia Press, 2004)
"Before the novel and the film Deliverance appeared in the early 1970s, any outsiders one met along the Chattooga River were likely serious canoeists or anglers. In later years, untold numbers and kinds of people have felt the draw of the river's torrents, which pour down the Appalachians along the Georgia-South Carolina border. Because of Deliverance the Chattooga looms enigmatically in our shared imagination, as iconic as Twain's Mississippi - or maybe Conrad's Congo."